Aplikasi Pengajuan Perbaikan Kerusakan Perangkat Komputer Berbasis Web pada PT. PUSRI (Pupuk Sriwidjaja) Palembang - Imam Solikin; Tri Susanti (INTECH, 2025)
The rapid development of information technology requires companies to optimize their IT systems and infrastructure. PT. PUSRI Palembang is one company that realizes the importance of repairing and maintaining computers effectively and efficiently. Therefore, the web-based computer damage repair application application is designed to simplify the process of applying for computer damage repairs at PT. PUSRI Palembang. In making this application, the system development method used is the waterfall method. The stages carried out include needs analysis, system design, implementation, testing and maintenance. This application was designed using the PHP programming language and MySQL database. This application allows users to submit computer damage repair requests online. Users can fill out a submission form which consists of information about the type of damage, description of the damage, and location of the damage. After the user submits a request, IT technicians will receive a notification and can follow up on the request. Additionally, users can also track the status of their repair requests through this app. Apart from that, this application can also increase efficiency and effectiveness in computer maintenance at PT. PUSRI Palembang.